A Case Study on Pharma Sdn Bhd - Focusing on the Vitamin C Business - Alagappar, Ponmalar (1999)
In the past years, Pharma Sdn Bhd's revenue was depended on the toll manufacturing business as the major revenue contributor and over-the-counter (OTC) brands. However, the toll manufacturing contract expires in end of 1999 and the management decision was to phase out the toll manufacturing business by the end of 1999 and venture into the ethical market. The ethical business was to start earning revenue in late 1998, with investments breaking even in the year 2002. With the loss of in come from toll manufacturing business, alternative revenue was needed to sustain the company until the ethical range starts contributing positively in the year 2003. Pharma Sdn Bhd is now depended on the OTC business sector for revenue, particularly on the brand Freesia which is a 20 year old brand and currently the market leader in chewable Vitamin C for the adult market. The OTC business sector will be the major revenue contributor for the next five years (1999 - 2003). The Vitamin C market is highly competitive as many players intensely compete in the open market and direct selling market. Furthermore, new entrants can easily enter the Malaysian market as currently there is no tax imposed on imported Vitamin C nor restrictions on the registration of products. Vitamin C is a vulnerable product to substitution and the chewable Vitamin C products are undifferentiated and standardised allowing consumers to alternate between brands very easily. Pharma Sdn Bhd, as the market leader of the adult Vitamin C, is faced with a gradual loss of market share. This is reflected by sales performance of Freesia which was well below the budgeted sale in the year 1998. Another note for concern here, is that the sale of the existing product, have deteriorated whilst competitors had shown a growth of 5% to 10% for their existing brands. To be able to sustain it's position as the market leader, the company needs to develop a differentiated and sustainable strategy and apply common sense and experience to understand competitors' moves, if not, the company could loose vital market share in an overnight instance.